2019
DOI: 10.1186/s13048-019-0500-x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic change due to combined treatment with myo-inositol, D-chiro-inositol and glucomannan in polycystic ovarian syndrome patients: a pilot study

Abstract: BackgroundPolycystic ovarian syndrome (PCOS) is a highly variable syndrome and one of the most common female endocrine disorders. Although the association inositols-glucomannan may represent a good therapeutic strategy in the treatment of PCOS women with insulin resistance, the effect of inositols on the metabolomic profile of these women has not been described yet.ResultsFifteen PCOS-patients and 15 controls were enrolled. Patients were treated with myo-inositol (1.75 g/day), D-chiro-inositol (0.25 g/day) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 72 publications
1
24
0
Order By: Relevance
“…Instrumental analyses were performed with a GC-MS system (GC-2010 Plus gas chromatograph and QP2010SE mass spectrometer; Shimadzu Corp., Kyoto, Japan). The analytical details are reported in Troisi et al [21][22][23][24][25][26].…”
Section: Metabolite Extraction Derivatization and Analysismentioning
confidence: 99%
“…Instrumental analyses were performed with a GC-MS system (GC-2010 Plus gas chromatograph and QP2010SE mass spectrometer; Shimadzu Corp., Kyoto, Japan). The analytical details are reported in Troisi et al [21][22][23][24][25][26].…”
Section: Metabolite Extraction Derivatization and Analysismentioning
confidence: 99%
“…The results were consistent with the study conducted by Troisi et al, Ozay et al and Regidor et al presenting reduction in testosterone levels with the administration of myoinositol and d-chiroinositol. 8,11,12 Tiwari et al also observed similar trends in testosterone levels at 6 months in metformin group. 13 The mean random blood glucose at baseline was 108.84± 11.08 and 87.07±4.48 which decreased to 100.64±7.73 and 82.57±2.26 after final follow up at 9 months in group 1 and 2 respectively.…”
Section: Resultsmentioning
confidence: 60%
“…identified increased levels of lactic acid in lean and overweight PCOS women and decreased levels in obese PCOS women, suggesting an augmented muscle insulin-stimulated glucose use in lean, but not obese women with PCOS (19,20). This difference may indicate that IR might be more severe and extensive in obese patients (19,20).…”
Section: Carbohydrate Metabolism In Obese Pcos Gc-ms-based Metabolomimentioning
confidence: 98%